EDUKASI PRENATAL ATTACHMENT DAPAT MENINGKATKAN KELEKATAN IBU DAN JANIN PADA IBU HAMIL RISIKO TINGGI - Mariani Mariani; Shinta Wahyusari; Nova Hikmawati (Jurnal Ilmiah Perawat Manado (Juiperdo), 2020)
Introduction: The prevalence of high-risk pregnancies in Indonesia is still quite high. Mothers who suffer from illness and pregnancy complications can influence the outcome of the pregnancy, which risks the occurrence of maternal and fetal morbidity and mortality. The psychological effects of high-risk pregnancies are anxiety, stress, and the mother experiences a crisis that can affect the relationship between mother and fetus. These conditions can continue in the relationship between mother and baby after birth. Therefore there needs to be an effort to increase the attachment of the mother and fetus, one of which can be done by providing education. This study aims to determine the effect of prenatal attachment education on maternal and fetal attachment in high-risk pregnant women in Paiton Subdistrict, Probolinggo Regency. Method: The study was conducted in Paiton Subdistrict, Probolinggo Regency in Mei-Juni 2019. The research method used was quasy experiment using pre-post test design. The population in this study were all high risk pregnant women in Dringu Subdistrict, Probolinggo Regency. The sampling technique used in this study was purposive sampling by determining the sample in accordance with the inclusion criteria. The number of samples to be used was 20 respondents. Data collection techniques using a questionnaire. Data were analyzed using Wilcoxon using SPSS. Results and Analysis: The results obtained showed the average score of attachment of the mother and fetus before the intervention was 52.15 and after the intervention was 60.50. There was a significant difference in the attachment of the mother and fetus before and after the intervention with a p value of 0,000 (p <0,000). Discussion: Prenatal care education needs to be included in the prenatal classroom program and started being given to pregnant women since the first trimester. Keywords: attachment, prenatal attachment, high risk pregnant women